The influence of geometric patterns on primary stability and os-seointegration of dental implant: a review of the literature - Nayana Prabhu, Krishna Kumar, Gautam Jaladi*, Amina Barkallah (International Journal of Advanced Science and Technology, 2020)
The overall performance of an implant could be influenced by design parameters like macro design and micro design and could thereby affect the implant success. Synergistic combinations of many bio-mechanical variables contribute to the effectiveness of the implant. The article reviews the existing state of literature in relation to the influence of geometric patterns, design and surface characteristics of the dental implant.The purpose of this review is to examine macro design features like thread geometry, thread pitch, helix angle, thread depth and thread width as well as implant crestal module on the primary stability and osseointegration of the dental implant.